Glycemic variability in patients with gastrointestinal cancer: An integrative review. (October 2020) - Mandolfo, N.; Berger, A.; Hammer, M.
Abstract: Purpose: Glycemic variability is associated with risks for adverse events in patients with cancer. Several studies have evaluated the presence and impact of hyperglycemia and/or hypoglycemia in patients with cancer; however, few studies have evaluated glycemic variability. The purpose of this integrative review of studies in patients with gastrointestinal cancers was to investigate the presence and methods of reporting glycemic variability during and following treatments. Methods: A comprehensive review of the literature was conducted. PubMed, CINAHL, EMBASE, and Cochrane databases were searched for publications between 1/1/1969 and 7/24/2019. Studies of patients with gastrointestinal cancer following surgery, during treatment, and <5 years following treatment were included and evaluated by cancer type and method of glucose and glycemic variability measurement. Results: Among 1526 patients with gastrointestinal cancer across 19 studies, gastric and pancreatic cancers were most prevalent. Timing of glucose testing and methods of analyzing glycemic variability varied. Most analyses used the standard deviation or interquartile range. Glycemic variability was more prevalent among patients with Type 2 Diabetes and among those with pancreatic cancer. In some patients glycemic variability remained notable > one year following surgery despite improvements in glycemic control. Conclusion: Patients with gastrointestinal cancer experience glycemic variability during and up to one year following treatment. There was heterogeneity in methods related to timing of testing and reporting glycemic variability among the 19 studies in this review. Future investigations need to identify the presence and define the methods of measuring glycemic variability in patients with gastrointestinal cancer. Highlights: Risks of glycemic variability in patients with cancer include increased rates of infection and mortality. Glycemic variability is present up to one year in patients with gastrointestinal cancer and is more prevalent in those with pancreatic cancer and those with Type 2 Diabetes. Investigations are needed to identify the presence and define the methods of measuring glycemic variability in patients with gastrointestinal cancer. Oncology nurses and the health care team can influence the standardization of reporting glycemic variability.